Chemical stability of hydrogen boride sheets against water: A density functional theory study - Rojas, Kurt Irvin M. (Animo Repository, 2020)
Hydrogen boride (HB) sheets is a recently synthesized material. With its novelty, various properties have not been explored yet. In this work, the stability of HB sheet was evaluated against water due to its presence across different applications, environment, and solutions. In addition, HB sheets with vacancy defects were examined and evaluated for water stability. The chemical stability was evaluated using density functional theory calculations. Among the considered vacancy defects, the H and B vacancies have the least formation energy requirement, and thus, are most likely to appear. The study conclusively shows that HB sheet (pristine and defected) is chemically stable against water as supported by the low adsorption energy and lack of chemical bonding. In the case of defected HB sheet, an adsorption energy higher than the pristine HB sheet case was observed and could be attributed to the increase dipole-dipole interaction due to the presence of vacancies. Therefore, this work shows that HB sheet will not passively react with water and is open to future application involving water.